(untitled) (Pain medicine, 2020)
Trigeminal neuralgia (TN) is the most common neuralgia, among others. In the Medical Center of Yuriy Spizhenko LLC from 2013 to 2020, 24 patients with TN were treated using the CyberKnife unified robotic system for radiosurgical treatment. This system is the maximum accuracy of <1 mm of receiving a therapeutic dose in a pathological tissue with minimal exposure to surrounding tissues due to a sharp drop in the dose gradient. A positive effect of the treatment was observed in 19 patients. 4 patients did not notice any improvement in their condition, an additional rhizotomy was performed, and 3 patients underwent drug blockade and continued taking carbamazepine. The CyberKnife robotic system for radiosurgical treatment is a safe, effective alternative to invasive surgical intervention, without the need for additional rehabilitation period and improves the patient’s quality of life